Formulasi Perancangan Strategi Pengembangan Usaha pada UMKM Gula Dezan Berkah dengan Business Model Canvas dan Analisis SWOT - Rohmawati, Siti; Wijaya, Fanji (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This study aims to provide a business strategy for developing a business for UMKM Gula Dezan Berkah to see the weaknesses that the company has and get solutions to any existing problems; in this case, UMKM Gula Dezan Berkah must be able to innovate and be able to see opportunities and threats, with SWOT Analysis and Business Model Canvas as an effort to increase sales. In conducting research, UMKM Gula Dezan Berkah applied qualitative research methods using a descriptive approach. Data collection in this study is based on direct analysis, interviews with business owners, references to scientific journals, electronic books, and several other sources confirmed to be true after being collected into data in document studies. With the business model canvas, the research results obtained several recommendations from the SWOT analysis to achieve business development targets at UMKM Gula Dezan Berkah. Some of the results of the business model canvas proposal are in the Value Proposition section to use packaging that is more attractive than before, then in the Customer Relationship section to not only market products directly but can be through social media or online store applications and so on, of course with the best service, and in the Channels section to offer street vendors, and local traditional markets to introduce products directly, and increase sales in online shop